Tradisi Pesantren : Antara Tradisionalis Dan Modernis (Studi Kasus Implikasi Kepemimpinan Kiai Pesantren Di Sumatera Selatan) - salni fajar (Medina-te : Jurnal Studi Islam, 2018)
The results of this study show leadership theory proposed by Max Weber and the type of leadership in an educational organization namely Weber which divides leadership patterns based on their dominance theory into three, namely traditional, charismatic, and rational leadership. It turns out that in practice the leadership of the kiai in pesantren has a very important role to advance the world of education in boarding schools. But what is also important is the educational background of the clerics and the environment where the kiai is. The type of kiai leadership in Islamic Boarding School Nurul Islam by kiai Syazali uses a type of traditionalist charismatic leadership and in certain moments uses an autocratic and democratic pattern, in the curriculum it has combined between salafiyah and modern, it can be seen from the inclusion of several government curricula, both from the Education Office and the Ministry Religion. Whereas the type of leadership applied by the cleric Tol'at is a type of modernist rational leadership, and at certain times intructive and coordinative patterns are used by scholars and practicing politics. So that it has implications for the activities of the pesantren both concerning the regeneration of leadership, the learning system, the value system and the network of kiai in society, to the kiai with practical politics. It is increasingly interesting to explore this dissertation further, so that the Malay traditions in South Sumatra appear to be correct.